A new species of the genus Neotropiella Handschin, 1942 (Collembola: Neanuridae) from Peru - Palacios-Vargas J.G. (2020)
Background: Neotropiella is a genus of springtails which can be of medium size (2 mm) or relatively long (5 mm). These springtails live in leaf litter, under the bark of dead trees or in decomposing wood, mainly in the Neotropical Region and are often collected by litter samples on Berlese funnels or by pitfall traps. Most species have been described, based on relatively few specimens and chaetotaxy of several species is incomplete. New information: A new species within Neotropiella was discovered in recent pitfall trap collections from Peru. Neotropiella peruana sp. n. was taxonomically treated and studied under both phase contrast and scanning electron microscopy. It is similar to N. insularis from Brazil, but smaller with only 4 mandibular teeth (vs. 5) and with well-developed unguis lateral teeth. Intraspecific variation of the new species is provided. We also present the first DNA barcodes for the genus. © 2020 Palacios-Vargas J, Callohuari Y. This is an open access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. All Rights Reserved.